Impact of Tuberculosis Contact Investigation Education on Health Cadres’ Knowledge at Girisubo Center, Gunungkidul, Yogyakarta, Indonesia - Rasyida, Zahra; Sofiana, Liena; Oktaviana, Ardyawati Wira (Journal of Community Medicine and Public Health Research, 2025)
Tuberculosis (TB) is an infectious disease that remains a worldwide health concern, with Indonesia having the secondhighest number of cases in the world. Contact investigation is a crucial tool for the early diagnosis and prevention of tuberculosis transmission, and health cadres play a vital role in this process. However, a lack of training reduces their efficiency in discovering instances. This study investigates the impact of IC training on cadre knowledge at the Girisubo Health Center, which had the highest number of TB patients in Gunungkidul in 2022. With most cadres not yet trained, this training will deepen their understanding and support TB case detection. This quasiexperimental study used a One-Group Pretest-Posttest design to investigate the influence of TB contact investigation training on the knowledge of 48 health cadres at the Girisubo Health Center. A validated questionnaire was used to gather data before and after the exam. A paired t-test with a 95% significance level (p<0.05) was used to assess changes in knowledge following training. This study found that TB patient contact investigation education was beneficial for the understanding of health cadres (p-value = 0.000; 95% CI: 2.962-5.643). TB contact investigation education improves cadres’ knowledge at the Girisubo Health Centre. The rise in post-test scores demonstrates the efficacy of lecture, audiovisual, and role-playing modalities. Interactive talks help alleviate boredom and improve comprehension. Continuous assistance is required to optimize the role of cadres in TB detection. tuberculosis contact investigation education was effective in increasing health cadres’knowledge regarding contact investigation.